Modulation of Keratocyte Phenotype by Collagen Fibril Nanoarchitecture in Membranes for Corneal Repair - Guo, Qiongyu (Biomaterials, 2013)
Type I collagen membranes with tailored fibril nanoarchitectures were fabricated through a vitrification processing, which mimicked to a degree, the collagen maturation process of corneal stromal extracellular matrix in vivo. Vitrification was performed at a controlled temperature of either 5 °C or 39 °C at a constant relative humidity of 40% for various time periods from 0.5 wk up to 8 wk. During vitrification, the vitrified collagen membranes (collagen vitrigels, CVs) exhibited a rapid growth in fibrillar density through the evaporation of water and an increase in fibrillar stiffness due to the formation of new and/or more-stable interactions. On the other hand, the collagen fibrils in CVs maintained their D-periodicity and showed no significant difference in fibrillar diameter, indicating preservation of the native states of the collagen fibrils during vitrification. Keratocyte phenotype was maintained on CVs to varying degrees that were strongly influenced by the collagen fibril nanoarchitectures. Specifically, the vitrification time of CVs mainly governed the keratocyte morphology, showing significant increases in the cell protrusion number, protrusion length, and cell size along with CV vitrification time. The CV vitrification temperature affected the regulation of the gene expressions of keratocyte fibroblasts, including keratocan and aldehyde dehydrogenase (ALDH), demonstrating a unique way to control the expression of specific genes in vitro.